RITUAL POAGO KAMPO PADA MASYARAKAT DESA INULU, KECAMATAN MAWASANGKA TIMUR, KABUPATEN BUTON TENGAH - Awat, Rustam (Jurnal Pendidikan Sejarah, 2023)
The aims of this research are 1) To find out the background to the poago kampo ritual in the people of Inulu Village, East Mawasangka District, Central Buton Regency; 2) To find out the procedures for carrying out the poago kampo ritual among the people of Inulu Village, East Mawasangka District, Central Buton Regency; 3) To describe the meaning contained in the poago kampo ritual among the people of Inulu Village, East Mawasangka District, Central Buton Regency. This research uses a qualitative descriptive research method. Data sources in this research are observation, interviews, documentation and literature. The research results show that: 1) The background to the emergence of the poago kampo ritual is caused by the change of seasons from west to east, and vice versa. Usually this change of season causes the emergence of seasonal diseases, therefore this change of season is carried out by village healing (poago kampo ritual). This is also carried out taking into account the geographical factors of the village, so this ritual is carried out in the west and east seasons. This ritual is carried out to treat villages that are being hit by seasonal diseases in the hope that after the community performs the poago kampo ritual, the seasonal diseases that attack the village will go away and will not return again. 2) The procedure for carrying out the poago kampo ritual is: The first stage, the preparation stage which includes determining the time and preparing the materials. This determination of good/bad days is manifested in all activities. This process cannot be separated from the process of calculating days which are considered to have good values and are kept away from disaster. Next, the preparation of ingredients for the poago kampo ritual, consisting of: free-range chicken eggs, cigarettes, betel leaves, betel lime, areca nut, young coconut, white cloth, rice, and lapi leaves. The second stage is the implementation stage after determining a good day and preparing the offering materials, then the offerings are placed in places that are considered sacred by the people of Inulu Village, which consists of five sacred places, namely under a big tree, in the center of the village, the cemetery area , beach area, and village border area. After placing the offerings by religious and traditional leaders as well as several community leaders, the final stage was to return to the kamokula house for the reading of prayers led by the kamokula; 3) The meaning contained in the poago kampo ritual is religious meaning (reciting prayers to reject evil), social meaning (showing the spirit of mutual cooperation), cultural meaning (ancestral traditions of the Inulu Village community) which are still preserved to this day.